Ocular bacterial signatures of exophthalmic disease in farmed turbot (Scophthalmus maximus). (25th February 2020) - Feng, Huawei; Zhang, Li; Ai, Haixin; Zhang, Xingang; Li, Shimeng; Yang, Tianzhou; Zhao, Jian; Qi, Mengyuan; Liu, Hongsheng
Abstract: As is the case at other sites in the body (e.g. the gut, skin and mouth), the ocular microbiota plays a crucial role in their host, as disturbances of the composition and function of the ocular microbiota are known to be associated with ocular disorders. Exophthalmic disease (ED) is a significant cause of high mortality in fish species, including farmed turbot ( Scophthalmus maximus ). However, the relationship between alterations in the ocular microbiota and ED in turbot is unclear. In this work, we collected turbot samples from farmed ponds with ED and healthy samples to understand changes in the ocular microbiota of turbot suffering from ED. We compared the structural and metabolic differences of ocular bacterial communities from farmed turbot with exophthalmic disease and those of healthy controls. Besides less microbial diversity found in turbot with ED regarding the control group, we also found that Aeromonas was the dominant bacteria both in controls and ED samples, but the abundance of Aeromonas was significantly greater in ED individuals. Moreover, the results of correlation test further suggest that Aeromonas overgrowth was correlated with the progress of the disease and shifts in ocular microbiota functional pathways in turbot. These findings emphasize that an increased abundance of Aeromonas serves as an ocular bacterial signature associated with ED in turbot, which provide basic information useful for diagnoses, prevention and treatment of ocular diseases occurring in cultured fish.